Adoptive transfer of siRNA Cblb-silenced CD8+ T lymphocytes augments tumor vaccine efficacy in a B16 melanoma model. - Reinhard Hinterleitner; Thomas Gruber; Christa Pfeifhofer-Obermair; Christina Lutz-Nicoladoni; Alexander Tzankov; Manfred Schuster; Josef M Penninger; Hans Loibner; Günther Lametschwandtner; Dominik Wolf; Gottfried Baier (PLoS ONE)
The ubiquitin ligase Cbl-b is an established regulator of T cell immune response thresholds. We recently showed that adoptive cell transfer (ACT) of cblb(-/-) CD8(+) T cells enhances dendritic cell (DC) immunization-mediated anti-tumor effects in immune-competent recipients. However, translation of cblb targeting to clinically applicable concepts requires that inhibition of cblb activity be transient and reversible. Here we provide experimental evidence that inhibition of cblb using chemically synthesized siRNA has such potential. Silencing cblb expression by ex vivo siRNA transfection of polyclonal CD8(+) T cells prior to ACT increased T cell tumor infiltration, significantly delayed tumor outgrowth, and increased survival rates of tumor-bearing mice. As shown by ex vivo recall assays, cblb silencing resulted in significant augmentation of intratumoral T cell cytokine response. ACT of cblb-silenced polyclonal CD8(+) T cells combined with DC-based tumor vaccines predominantly mediated anti-tumor immune responses, whereas no signs of autoimmunity could be detected. Importantly, CBLB silencing in human CD8(+) T cells mirrored the effects observed for cblb-silenced and cblb-deficient murine T cells. Our data validate the concept of enhanced anti-tumor immunity by repetitive ACT of ex vivo cblb siRNA-silenced hyper-reactive CD8(+) T cells as add-on adjuvant therapy to augment the efficacy of existing cancer immunotherapy regimens in clinical practice.